FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP PENGGUNAAN SWAP SUKU BUNGA (Studi Pada Bank Konvensional di Indonesia) - Dewi, Kadek Leny Puspita; Abundanti, Nyoman (E-Jurnal Manajemen, 2017)
The purpose of this study was to determine the factors that influence the use of Interest Rate Swaps on Conventional Banks in Indonesia 2011-2015. This study uses independent variables are Bank Size, Asset Quality (NPL), Return Performance (ROA), Interest Rate Risk (NIM), Institutional Ownership and Interest Rate Swaps as the dependent variable. There are 16 conventional banks as sample using purposive sampling method. Data analysis technique used is Multiple Linear Regression Analysis. The results of this study provide evidence that Bank Size and ROA has a negative and significant impact on the use of Interest Rate Swaps, NPL has a positive and significant impact on the use of Interest Rate Swaps, while the NIM has a negative effect and no significant and Institutional Ownership has a positive influence and not significant the use of Interest Rate Swaps.
Keywords: conventional banks; interest rate swaps